The effect of diffusion on lithium isotope ratios in Icelandic basalts - Marshall, Edward W.; Halldórsson, Sæmundur A.; Tian, Liyan; Jackson, Matthew G.; Jenner, Frances; Stefánsson, Andri (Chemical Geology, 2024)
In recent years, diffusion has gained increasing recognition as an important process for explaining the lithium (Li) isotope ratios (δ7Li) of magmatic systems. However, the role of diffusion in explaining the variability of mantle-derived basalts has not yet been investigated in detail. We have measured δ7Li values in a comprehensive suite of fresh, subglacial Icelandic basalt glasses and observe a wide range of values from 2.4‰ to 7.3‰, the largest range in Li isotope compositions identified at any ocean island. We find that δ7Li values do not correlate with lithophile element tracers, but do correlate with 3He/4He. One possibility is that the high diffusivities of both Li and He permit fractionation of Li isotope compositions that couple it to 3He/4He, and decouple it from other, slower-diffusing lithophile tracers. In this study, we explore this idea and model diffusive processes in crystal mushes and mantle melt channels, both with and without melt transport. Our modelling indicates that large (>3‰) fractionation of Li isotope compositions from MORB-like values can be generated by diffusion and that the coupling of Li isotope ratios and 3He/4He signatures can occur as a consequence of diffusive interactions within mantle melt channels. This suggests that the Li isotope compositions of melts cannot be used as a straightforward passive tracer of mantle heterogeneity, because they can be fractionated during magmatic processes. In contrast, we find that diffusive fractionation of 3He/4He is small (∼1 Ra) next to the variability in Icelandic basalts (∼8 to ∼35 Ra). Diffusive fractionation of Li isotope ratios should be most pronounced at OIB localities whose mantle melts have a wide range of [Li], such as Hawaii and Iceland. Although a mantle source can contain Li isotope heterogeneities as a result of crustal recycling, we show that a mantle that is homogenous in Li isotope composition can still generate melts that have variable δ7Li values via diffusion processes. The same diffusion models can also be applied to other stable isotope systems such as H, Mg, Ca, and Fe. Indeed our models show that diffusion during magmatic transport within the mantle may be a significant source of “noise” in the δ7Li, δD, and possibly δ26Mg isotopic systems.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Basalt; Iceland; Lithium isotopes; Mantle geochemistry; Stable isotope